2013
DOI: 10.1016/j.renene.2013.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening the palm oil biomass Renewable Energy industry in Malaysia

Abstract: HighlightsWe recommend a fuel collection hub and explore the potential use of less sought after large fibre and palm frond. We suggest centralising a technology hub facility to encourage conversion to a low carbon technology at the existing mills. Smart-partnership collaboration for building a large-scale biomass plant is worth consideration as it lowers the business risks and enhances economies of scale. Off-grid solutions involving decentralized generation would help to avoid further grid infrastructure inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(40 citation statements)
references
References 24 publications
0
36
0
1
Order By: Relevance
“…All the plant operators used palm kernel shell and mesocarp fibre for power generation and were not currently using EFB as boiler fuel. The situation in Sarawak's mills is in contrast with practice in palm mills in Peninsular Malaysia where EFB is also used as boiler fuel, along with palm kernel shells and mesocarp fibres [32]. None of the respondents used EFB as boiler fuels mainly because of its bulkiness and high moisture content, which requires pre-treatment before being used as boiler fuel.…”
Section: Sustainability Of Biomass Supply Chainmentioning
confidence: 94%
See 1 more Smart Citation
“…All the plant operators used palm kernel shell and mesocarp fibre for power generation and were not currently using EFB as boiler fuel. The situation in Sarawak's mills is in contrast with practice in palm mills in Peninsular Malaysia where EFB is also used as boiler fuel, along with palm kernel shells and mesocarp fibres [32]. None of the respondents used EFB as boiler fuels mainly because of its bulkiness and high moisture content, which requires pre-treatment before being used as boiler fuel.…”
Section: Sustainability Of Biomass Supply Chainmentioning
confidence: 94%
“…Inconsistent boiler fuel supplies, such as kernel shells, Empty Fruit Bunch (EFB), and mesocarp fibres will affect the business of small developers who rely upon a third party's supply. Uncertainties related to long-term biomass supply will expose the market to fluctuating prices, as the major plantation developers dominate the market with full control according to their business model [32]. Based on the demographic profiles from the returned questionnaires, it was found that 94% of oil palm mills in the Sarawak Northern region are associated with major developers.…”
Section: Sustainability Of Biomass Supply Chainmentioning
confidence: 99%
“…Se conoce que un 78% en peso de los racimos cosechados representa los frutos y que el coeficiente de conversión de fruto a aceite crudo es de aproximadamente el 20% (González et al, 2015), puede estimarse que anualmente por cada hectárea se obtienen 3,14 t de aceite y 21,68 t de residuos, no contando el material foliar retirado de la planta al momento de la cosecha. Estas cifras han generado preocupación en muchos productores del sureste asiático y aún en Colombia, quienes optan por usar la biomasa para la generación de energía y vapor, principalmente, reduciendo en gran medida los costos energéticos, pero emitiendo gases y material particulado al ambiente (Yusoff, 2006;Umar et al, 2013;Briceño et al, 2015). Por consiguiente, y dado a que los residuos de la palma aceitera son diversos, es importante explorar e investigar la viabilidad de transformar de manera rentable desechos como los efluentes líquidos, capaces de generar biometano, bioetanol, fertilizantes o biohidrógeno mediante el uso de microorganismos, la torta de palmiste en la elaboración de concentrado para animales, y en especial la transformación de la biomasa que se obtiene en grandes cantidades, en la elaboración de biocompuestos o en la elaboración de muebles.…”
Section: Manejo De Desechos De La Industria De La Palma Aceiteraunclassified
“…Overall, the final grid-connected capacity under the SREP regime ended up at 65 MW, which is certainly far behind the original capacity target of 350 MW envisaged early in the 9th Plan (2006). Biomass residues, particularly from oil palm plantations, contribute the most with 40 MW of gridconnected capacity [31,32], outweighing other renewable resources as shown below:…”
Section: The Small Renewable Energy Power (Srep) Programmementioning
confidence: 99%